Communicating food-based dietary guidelines culturally sensitive? A comparative argumentation analysis of the German and Brazil dietary guidelines - Helmus, Imke; Bartelmeß, Tina (Frontiers in Communication, 2025)
ObjectiveTo examine the cultural appropriateness and argumentation structure of food-based dietary guidelines (FBDGs) in Germany and Brazil, with the aim of identifying areas for improvement to better align with sociocultural contexts and enhance their impact on dietary choices and public health.DesignA comparative study utilizing the concepts of cultural health communication and culturally sensitive argumentation to analyze the communication materials of FBDGs in both countries.SettingThe analysis focuses on the national FBDGs and associated communication strategies employed in Germany and Brazil.ParticipantsThe study examines how FBDG materials are communicated to policymakers and the general public in Germany and Brazil, without direct participant involvement.ResultsThe Brazilian Dietary Guidelines (BDGs) show a more complex and culturally sensitive argumentation structure than the German Dietary Guidelines (GDGs). They incorporate multi-layered reasoning and culturally rooted examples, aligning dietary recommendations closely with Brazilian food traditions and social norms. In contrast, the GDGs emphasize scientific authority and offer more straightforward, less culturally embedded arguments. This highlights the BDGs’ stronger alignment with local values and practices.